SYNTHESIS AND COORDINATION CHEMISTRY OF AZULENE-BASED TRIDENTATE PINCER LIGANDS - Akindele, Toluwanimi Lydia (Nazarbayev University School of Sciences and Humanities, 2025)
A series of azulene-based tridentate ligands; 1,3-bis(2-pyridyl)azulene (15), 1,3-bis(benzothiazole-2-yl)azulene (16), and 1,3-bis(imino)azulene (17), were synthesized and explored for their coordination chemistry with Group 9 and 10 transition metals and their photophysical properties. Their structural and optical properties were studied and characterized by 1H, 13C-NMR, HSQC, and UV-vis spectroscopy. Metalation of ligands (15) and (17) with [Rh(Cl)(C2H4)2]2 suggested the formation of their corresponding d6-Rh(III) complexes. The appearance of non-coordinated ethylene at 5.25 ppm and disappearance of azulene C2-H proton at 8.4 ppm and the appearance of the ethyl groups indicated by the triplet and quartet in the aliphatic region support this claim Also, efforts to access the corresponding Ir(III) complex via oxidative addition of [IrCl(COD)]₂ to (17) resulted in the formation of a non-symmetric imine-bound Ir(I) species, with no observable C–H activation at the azulene core. Metalation of (17) with NiBr2(CH3CN)2 under varied solvent and temperature conditions. Firstly, in THF, we observed the disappearance of imine protons, indicative of the disappearance of the C2-H singlet initially observed at 9.4 ppm, which implies the rapid, reversible intermolecular exchange between the imine and alkene protons. Secondly, in acetonitrile, we observed nickel’s coordination to one of the imine nitrogen rather than the C2 position of the ligand, indicative of the downfield shift of the imine protons and the appearance of the C2-H azulene proton. Collectively, these observations suggest that Ni(II) atomic radii might be too small to coordinate the two imine nitrogen due to the large bite angle of the ligand. UV–Vis absorption spectroscopy of the free ligands and their corresponding Rh(III) complexes revealed a broadening of peaks upon coordination of the ligand with the Rh metal center. This suggested the existence of MLCT(metal-to-ligand charge transfer) from the metal to the π-system of the azulene core. Future studies will focus on modifying the ligand backbone to fine-tune the bite angle and its electronic environment, exploring heavier transition metals with expanded coordination geometries, higher oxidation potentials, and employing low-temperature NMR techniques to resolve dynamic processes within metal-ligand systems.
Keywords: type of access: embargo; azulene; pincer ligands; transition metal complexes; photocatalysis